miRNA-124 in Immune System and Immune Disorders - Qin, Zhen; Wang, Peng-Yuan; Su, Ding-Feng; Liu, Xia (Frontiers in Immunology, 2016)
In recent years, miR-124 has emerged as a critical modulator of immunity and inflammation. Here, we summarize studies on the function and mechanism of miR-124 in the immune system and immunity-related diseases. They indicated that miR-124 exerts a crucial role in the development of immune system, regulation of immune responses, and inflammatory disorders. It is evident that miR-124 may serve as an informative diagnostic biomarker and therapeutic target in the future.